2009
DOI: 10.1148/radiol.2502080574
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Four Embolic Materials at Uterine Artery Embolization by Using Postprocedural MR Imaging Enhancement

Abstract: Patients treated with Bead Block or Contour SE demonstrated a reduced degree of infarction at follow-up MR imaging compared with patients treated with Contour or Embosphere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 12 publications
1
19
1
3
Order By: Relevance
“…Procedural factors identified that may minimize pain after UAE include selection to avoid bilateral UAE among patients with limited fibroid disease [6], type of embolic material used, Contour SE requiring less opioid analgesia compared to Embosphere/Embosphere Gold [7,8] and the use of preemptive analgesic, anti-inflammatory and antiemetic medications.…”
Section: Introductionmentioning
confidence: 99%
“…Procedural factors identified that may minimize pain after UAE include selection to avoid bilateral UAE among patients with limited fibroid disease [6], type of embolic material used, Contour SE requiring less opioid analgesia compared to Embosphere/Embosphere Gold [7,8] and the use of preemptive analgesic, anti-inflammatory and antiemetic medications.…”
Section: Introductionmentioning
confidence: 99%
“…The first embolic agent available for UAE was non spherical polyvinyl alcohol (nPVA) particles (Contour; Target Vascular/Boston Scientific, Natick, MA,USA). Following that, several embolic agents have been used successfully for UAE, such as tris-acryl microspheres, gelatin sponge, and various types of microspheres (5)(6)(7)(8)(9)(10). Several recent studies have shown that the nature of the embolic agent does make a difference in the effect of UAE on tumors (11).…”
Section: Introductionmentioning
confidence: 99%
“…After selective catheterization of the bilateral uterine arteries, uterine artery angiography was carried out to enable identification of the vasculature and parenchyma of the uterus. Embolization was performed in free flow: 0.1 mL of each embolic material (PVA particles and calibrated SPIO-embedded chitosan microspheres) was suspended in 4.9 mL of a mixture of iodinated contrast medium (Visipaque, GE Healthcare, Princeton, New Jersey, USA) and normal saline (1:1, v/v); this mixture was diluted to a concentration, 3.5 to 4.0 times lower than that used in clinical practice (11).…”
Section: Angiography and Embolization Protocolmentioning
confidence: 99%